2017
DOI: 10.1212/wnl.0000000000003980
|View full text |Cite
|
Sign up to set email alerts
|

BDNF Val66Met predicts cognitive decline in the Wisconsin Registry for Alzheimer's Prevention

Abstract: Objective: To examine the influence of the brain-derived neurotrophic factor (BDNF) Val66Met polymorphism on longitudinal cognitive trajectories in a large, cognitively healthy cohort enriched for Alzheimer disease (AD) risk and to understand whether b-amyloid (Ab) burden plays a moderating role in this relationship.Methods: One thousand twenty-three adults (baseline age 54.94 6 6.41 years) enrolled in the Wisconsin Registry for Alzheimer's Prevention underwent BDNF genotyping and cognitive assessment at up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 41 publications
10
52
0
Order By: Relevance
“…In age-matched mutation non-carriers who showed no evidence of amyloidosis, rates of cognitive decline, hippocampal volume loss, increases in CSF tau and ptau 181 , and cortical Aβ accumulation did not change with increasing age for either Met66 carriers or Val66 homozygotes (Figure 2). This is consistent with observations by us, 68 and others 9 that BDNF Val66Met has no effect on cognitive decline or hippocampal volume loss in β-amyloid-negative adults. The necessity of β-amyloid positivity for cognitive decline in Met66 carriers led us to propose that equivocal findings on the effect of BDNF Val66Met on cognitive decline observed in previous studies, 20 is likely due to their not accounting for the presence of β-amyloid positivity in their samples.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In age-matched mutation non-carriers who showed no evidence of amyloidosis, rates of cognitive decline, hippocampal volume loss, increases in CSF tau and ptau 181 , and cortical Aβ accumulation did not change with increasing age for either Met66 carriers or Val66 homozygotes (Figure 2). This is consistent with observations by us, 68 and others 9 that BDNF Val66Met has no effect on cognitive decline or hippocampal volume loss in β-amyloid-negative adults. The necessity of β-amyloid positivity for cognitive decline in Met66 carriers led us to propose that equivocal findings on the effect of BDNF Val66Met on cognitive decline observed in previous studies, 20 is likely due to their not accounting for the presence of β-amyloid positivity in their samples.…”
Section: Discussionsupporting
confidence: 93%
“…10 These results also accord with observations in preclinical and prodromal sporadic AD, where β-amyloid-positive Met66 carriers also showed faster cognitive decline and hippocampal volume loss when compared to β-amyloid-positive Val66 homozygotes. 69 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Val66Met single nucleotide polymorphism, exacerbates AD symptoms and biomarkers and other neurodegenerative brain disorders. 12 Taking these aspects into consideration, with a middle-aged cohort presenting enhanced risk-for-AD, the evidence showed that the carriage of the BDNF Met allele was associated with a sharper decline of episodic memory performance and executive function expressions and this decline was aggravated by the greater weight of the beta-amyloid biomarker (ibid). Furthermore, the reduced levels of BDNF in AD have been shown patients in comparisons with healthy control volunteers.…”
mentioning
confidence: 99%